Prevalence of mutations in the Plasmodium falciparum chloroquine resistance transporter, PfCRT, and association with ex vivo susceptibility to common anti-malarial drugs against African Plasmodium falciparum isolates - (:unkn) unknown (My University, 2020)
BackgroundThe Plasmodium falciparum chloroquine transporter gene (pfcrt) is known to be involved in chloroquine and amodiaquine resistance, and more particularly the mutations on the loci 72 to 76 localized within the second exon. Additionally, new mutations (T93S, H97Y, C101F, F145I, M343L, C350R and G353V) were recently shown to be associated with in vitro reduced susceptibility to piperaquine in Asian or South American P. falciparum strains. However, very few data are available on the prevalence of these mutations and their effect on parasite susceptibility to anti-malarial drugs, and more particularly piperaquine in Africa.MethodsA molecular investigation of these mutations was performed in 602 African P. falciparum parasites collected between 2017 and 2018 on malaria patients hospitalized in France after a travel in African countries. Associations between genotypes and in vitro susceptibilities to piperaquine and standard antimalarial drugs were assessed.ResultsNone of the mutations, previously described as associated with piperaquine resistance, was found in the 602 P. falciparum African isolates. The K76T mutation is associated with resistance to chloroquine (p < 0.0002) and desethylamodiaquine (p < 0.002) in Africa. The K76T mutation is not associated with in vitro reduced susceptibility to piperaquine. The mutation I356T, identified in 54.7% (n = 326) of the African isolates, was significantly associated with reduced susceptibility to quinine (p < 0.02) and increased susceptibility to mefloquine (p < 0.04). The K76T and I356T mutations were significantly associated in West African isolates (p = 0.008).ConclusionNone of the mutations in pfcrt found to be associated with piperaquine reduced susceptibility in Asia or South America (T93S, H97Y, C101F, F145I, M343L C350R and G353V) were found in the 602 African isolates including the three isolates with reduced susceptibility to piperaquine. The K76T mutation, involved i
Keywords: African Research